Equity Carve‐Outs and Managerial Discretion - Allen, Jeffrey W.; McConnell, John J. (Journal of Finance, 1998)
This study proposes a managerial discretion hypothesis of equity carve‐outs in which managers value control over assets and are reluctant to carve out subsidiaries. Thus, managers undertake carve‐outs only when the firm is capital constrained. Consistent with this hypothesis, firms that carve out subsidiaries exhibit poor operating performance and high leverage prior to carve‐outs. Also consistent with this hypothesis, in carve‐outs wherein funds raised are used to pay down debt, the average excess stock return of + 6.63 percent is significantly greater than the average excess stock return of −0.01 percent for carve‐outs wherein funds are retained for investment purposes.